A criminology of war? - McGarry, Ross; Walklate, Sandra (New horizons in criminology., 2019)
With the academic study of 'war' gaining renewed popularity within criminology in recent years, this book illustrates the long-standing engagement with this social phenomenon within the discipline. Foregrounding established criminological work addressing war and connecting it to a wide range of extant sociological literature, the authors present and further develop theoretical and conceptual ways of thinking critically about war.